Education at the crossroads: Reflecting on the new scenarios for teaching geography in the post-pandemic - Oliveira, Luã Karll (2021)
In the course of history, different civilizations have gone through serious structural crises that exposed human weaknesses, often evidenced by the worsening of social problems, such as inequalities, the intensification of barbarism, of poverty, of misery, violence an so many other ailments. Indeed, the pandemic makes us experience a new context, defined by a period of severe health crisis that reverberates in the different dimensions of human life and contributes to the deepening of socio-spatial inequalities on a planetary scale. In the light of this perspective, the present article is intended to address aspects related to education, with emphasis on the teaching of Geography, reflecting how this segment of society expresses itself in the face of the psychosphere created by the moment of instability resulting from the current context. Therefore, the perception that leads us to this analysis is based on two central questions. The first deals with the consolidation of educational practices as a reproduction factor of the capitalist system; and the second, deals with the teaching of Geography and the teaching role in the formative process of subjects in the post-pandemic.